STUDY ON THE EXTRACTION PROCESS OF TOTAL ANTHRAQUINONES IN RADIX ET RHIZOMA RHEI AND THEIR ANTILIPEMIC EFFECTS - Xie, Huichun; Shang, Jun (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Radix et Rhizoma Rhei has a gastric mucosal protective effect, major anti-gastritis and anti-peptic ulcer active constituents were emodin, aloe-emodin, chrysophanol, rhein, etc. The objective of the study was the extraction process of total anthraquinones in Radix et Rhizoma rhei and their antilipemic effects. Materials and Methods: Orthogonal experiment, UV spectrophotometry and conventional antilipemic effect determination method were used to optimize the extraction process, and to determine the total anthraquinone content, as well as blood levels of total cholesterol, triglycerides, HDL and LDL. Results: Ethanol concentration, extraction time and ethanol amount had significant influences on the extraction of total Radix et Rhizoma rhei anthraquinones, total Radix et Rhizoma rhei anthraquinones could significantly reduce blood levels of total cholesterol, triglycerides, HDL and LDL. Conclusion: The optimum extraction process was two times extraction of Radix et Rhizoma rhei with 70% ethanol, the amounts of solvent of 8 folds and 5 folds, successively, and the extraction time of 60 min each. In addition, this extract has an antilipemic effect in mice.